Joint detection and estimation for cooperative communications in cluster‐based networks. Issue 17 (6th October 2011) - Wang, Tsang‐Yi; Pu, Jyun‐Wei; Li, Chih‐Peng
ABSTRACT: A joint data detection and channel estimation scheme is proposed for cooperative communications in cluster‐based networks. In the proposed approach, each relay detects the source information using its joint detection and estimation rules and then compresses this information and forwards it to the destination node. The source information received from all the relays in the network is combined at the destination node in accordance with a fusion decision rule in order to determine the corresponding symbol vector. The joint detection and estimation rule at the relays and the fusion rule at the destination node are both processed using an expectation maximization algorithm. In order to reliably avoid poor local maxima, we utilized one pilot symbol per signal block to obtain a better initial starting point for the expectation maximization algorithm. The simulation results show that the feedback mechanism accelerates the convergence of the local channel estimates toward the Cramer–Rao lower bound. Copyright © 2011 John Wiley & Sons, Ltd. Abstract : In the proposed approach, each relay detects the source information using its joint detection and estimation rules, and then forwards it to the destination node. The source information received from all the relays is combined at the destination node in accordance with a fusion decision rule in order to determine the corresponding symbol vector. The joint detection and estimation rule at the relays and the fusion rule at the destination node are both processed using an expectation maximization algorithm.